Synthesis and Properties of a Lacquer Wax-Based Quarternary Ammonium Gemini Surfactant - Hongxia Chen; Chengzhang Wang; Jianzhong Ye; Hao Zhou; Li Lu; Zhibing Yang (Molecules, 2014)
Lacquer wax is an important fatty resource obtained from the mesocarp of the berries of Toxicodendron vernicifluum. In order to expand the applications of lacquer wax, we hydrolyzed it after establishing the best conditions for the acid-catalyzed hydrolysis using a Box-Behnken design. Then we synthesized a quarternary ammonium gemini surfactant by a three-step reaction. The surface properties of an aqueous solution of the final product were investigated. The optimum conditions were 9% catalyst, 100 °C of reaction temperature and 14 h of reaction time, while the maximum free fatty acids (FFA)% was 99.67%. From the gas chromatography, the main fatty acids of the lacquer wax were palmitic, oleic and octadecanoic acid. The lacquer wax gemini surfactant was synthesized, and its structure was confirmed by IR and NMR. The experiments showed that the critical micelle concentration (CMC) is 5 × 10−4 mol·L−1, the surface tension is 33.6 mN·m−1. When the content of surfactant was 0.1%, the separation time of 5 mL water was 10 min.